Conservation Policy Gaps in Transboundary Wildlife Corridors (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2022)
Transboundary wildlife corridors — linear habitat networks that connect protected areas across national boundaries —are essential for maintaining large carnivore and ungulate population connectivity in human-dominated European landscapes, yet their governance is typically fragmented across incompatible national legal frameworks that create policy gaps at international borders. This study conducted a systematic legal and policy analysis of 14 transboundary wildlifecorridor systems in Europe, covering 28 bilateral and multilateral conservation agreements across the borders of Sweden-Norway, Germany-Poland, Austria-Czech Republic, France-Spain, and Italy-France, combined with structured expert interviews (n = 84 conservation practitioners) and landscape connectivity modelling (Circuitscape 4.0) to identify and quantify policy gaps and their functional connectivity consequences. A policy gap index (PGI), integrating legal protection status, monitoring coordination, management harmonisation, and enforcement consistency, was computed for each corridor. Mean PGI across the 14 corridors was 0.58 ± 0.14 (scale 0–1; 0 = complete gap, 1 = full alignment),indicating moderate-to-high policy fragmentation across all study systems. Circuitscape connectivity modellingdemonstrated that policy gaps were spatially predictive of corridor pinch-points: effective resistance to wildlife movement was on average 2.4× higher at international borders with PGI < 0.40 compared to borders with PGI > 0.70 (t = 5.84, p < 0.001). Legal protection continuity was the single policy dimension with the largest independent effect on corridor connectivity (β = -0.62, p < 0.001 in multiple regression). Expert interviews identified data-sharing protocols, joint monitoring programmes, and harmonised land-use zoning as the three highest priority gaps in all 14 corridors. These findings quantify the connectivity costs of policy fragmentation in transboundary conservation and identify specific legaland governance interventions that would most efficiently restore corridor function under the EU Biodiversity Strategy 2030.